Fever, Haematuria, and Acute Graft Dysfunction in Renal Transplant Recipients Secondary to Adenovirus Infection: Two Case Reports - J. Ramírez; I. C. Bostock; A. Martin-Onraët; S. Calleja; A. Sánchez-Cedillo; L. A. Navarro-Vargas; A. L. Noriega-Salas; O. Martínez-Mijangos; N. O. Uribe-Uribe; M. Vilatoba; B. Gabilondo; L. E. Morales-Buenrostro; et al. (Case Reports in Nephrology)
We report two cases of adenoviral infection in kidney transplant recipients that presented with different clinical characteristics under similar demographic and posttransplant conditions. The first case presented with fever, gross haematuria, and acute graft dysfunction 15 days following renal transplantation. A graft biopsy, analyzed with immunohistochemistry, yielded negative results. However, the diagnosis was confirmed with blood and urine real-time PCR for adenovirus 3 days after the initial clinical manifestations. The immunosuppression dose was reduced, and ribavirin treatment was started, for which the patient quickly developed toxicity. Antiviral treatment allowed for transient response; however, a relapse occurred. The viral real-time PCR became negative upon immunosuppression reduction and administration of IVIG; graft function normalized. In the second case, the patient presented with fever and dysuria 1 month after transplantation. The initial imaging studies revealed graft enlargement and areas of hypoperfusion. In this case, the diagnosis was also confirmed with blood and urine real-time PCR for adenovirus 3 days after the initial clinical manifestations. Adenoviral nephritis was confirmed through a graft biopsy analyzed with light microscopy, immunohistochemistry, and PCR in frozen tissue. The immunosuppression dose was reduced, and IVIG was administered obtaining excellent clinical results along with a negative real-time PCR.